A Biologic Surgical Implant in Complex Abdominal Wall Repair: 3-Year Follow-Up Results of a Multicentric Prospective Study - Gossetti F (Dove Medical Press, 2021)
Francesco Gossetti,1 Nikolaus Zuegel,2 Pasquale Giordano,3 Rupert Pullan,4 Jochen Schuld,5 Paolo Delrio,6 Marco Montorsi,7 Olivier van Kerschaver,8 Jean Lemaitre,9 Ben Griffiths,10 Linda D’Amore1 1Department of Abdominal Wall Surgery, University Hospital (C/O Instituto Clinica Chirugica II), Rome, Italy; 2Visceral Surgery, Centre Hospitalier Emile Mayrisch, Esch-sur-Alzette, Luxembourg; 3Department of Colorectal Surgery, Whipps Cross University Hospital, Leytonstone, UK; 4Colorectal Surgery, Torbay Hospital, Torquay, UK; 5Clinic for General and Visceral Surgery, Universitätsklinikum des Saarlandes, Homburg, Germany; 6Department of Abdominal Oncology, Istituto Nazionale Tumori, Napoli, Italy; 7General Surgery, Humanitas University and IRCCS Humanitas Research Hospital, Milano, Italy; 8General Surgery, Algemeen Ziekenhuis Sint LUCAS, Gent, Belgium; 9Thoracic Surgery, CHU Ambroise Pare, Mons, Belgium; 10Colorectal Surgery, Royal Victoria Infirmary, Newcastle Upon Tyne, UKCorrespondence: Francesco GossettiDepartment of Abdominal Wall Surgery, University Hospital (C/O Instituto Clinica Chirurgica II), Policlinico Umberto I, Rome, 00162, ItalyEmail gossetti@tiscali.itPurpose: Despite the advancements in the reinforcement and closure techniques available, complex abdominal wall reconstruction (CAWR) remains a challenging surgical undertaking with considerable risk of postoperative complications. Biological meshes were developed that may help to complement standard closure techniques and offer an alternative to synthetic meshes, which carry significant risks with their use in complex cases.Patients and Methods: A total of 114 patients underwent surgical treatment for CAWR with a Permacol™ (a biologic surgical implant). The study objective was to evaluate the short-term (6 months), mid-term (12– 24 months), and long-term (36 months) clinical outcomes (through 36 months) associated with the use of a biologic surgical implant in these cases.Results: The cumulative hernia recurrence rate was 18.7% (17/91) at 24 months and 22.4% (19/85) at 36 months. Twelve (14.1%) subjects required reoperation for hernia repair within 36 months for repair of recurrent hernias. Between 6- and 36-months post-surgery, patients reported improvement in their Carolina comfort scale (CSS) measures of severity of pain, sensation of mesh, and movement limitations.Conclusion: A biologic surgical implant can provide long-term benefit to complex abdominal wall repairs in patients staged grade III according to the Ventral Hernia Working Group (VHWG).Keywords: Permacol, biologic surgical implant, complex abdominal wall repair